2008
DOI: 10.1083/jcb.200805045
|View full text |Cite
|
Sign up to set email alerts
|

ERK regulates Golgi and centrosome orientation towards the leading edge through GRASP65

Abstract: Directed cell migration requires the orientation of the Golgi and centrosome toward the leading edge. We show that stimulation of interphase cells with the mitogens epidermal growth factor or lysophosphatidic acid activates the extracellular signal–regulated kinase (ERK), which phosphorylates the Golgi structural protein GRASP65 at serine 277. Expression of a GRASP65 Ser277 to alanine mutant or a GRASP65 1–201 truncation mutant, neither of which can be phosphorylated by ERK, prevents Golgi orientation to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 29 publications
5
176
1
1
Order By: Relevance
“…The Golgi apparatus has emerged as a critical hub for intracellular signaling (34), and signaling is essential for Golgi polarization. For example, phosphorylation of the Golgi protein, GORASP1 (also known as GRASP65, a GM130 interaction partner), by the kinase ERK is required for Golgi reorientation (35). Interestingly, ERK activity has been shown to be modulated by CCM3 and MST4 (9); whether or not GORASP1 phosphorylation is modulated in our system remains to be tested.…”
Section: Discussionmentioning
confidence: 95%
“…The Golgi apparatus has emerged as a critical hub for intracellular signaling (34), and signaling is essential for Golgi polarization. For example, phosphorylation of the Golgi protein, GORASP1 (also known as GRASP65, a GM130 interaction partner), by the kinase ERK is required for Golgi reorientation (35). Interestingly, ERK activity has been shown to be modulated by CCM3 and MST4 (9); whether or not GORASP1 phosphorylation is modulated in our system remains to be tested.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the role of Golgi in cell polarization was better appreciated. Disruption of Golgi structure and positioning in the cell not only affects polarized secretion, but also affects centrosome orientation and polarity during cell migration (Bisel et al 2008;Yadav et al 2009). Taken together, as was the case in yeast budding and epithelial polarization, membrane trafficking is important for the maintenance of polarity during cell migration.…”
Section: Membrane Trafficking Of E-cadherinmentioning
confidence: 99%
“…This activity arose as the result of the tethering functions displayed by GRASP65 and GRASP55, through their interactions with their partner proteins GM130 and golgin-45, respectively (2)(3)(4). Several other studies have shown more recently that the GRASPs are involved in the maintenance of the structure of the Golgi ribbon in mammal cells during interphase, in controlling the fragmentation of the Golgi complex at the onset of mitosis (5)(6)(7)(8), in establishing cell polarity in migrating cells (9), and in the consumption of COPII vesicles and the formation of the cis-Golgi in yeast (10).…”
mentioning
confidence: 99%